Optimization of network device hardening in a multivendor environment - Ali Bello Imoukhuede; Tarek Rahil Sheltami; Asharf Hasan Mahmoud; Abdulaziz Yagoub Barnawi (Scientific Reports)
Abstract This paper presents a Python-based Nornir framework for automating network device hardening in multi-vendor environments, addressing critical gaps in scalability and interoperability. Unlike existing single-vendor solutions, our method enforces CIS benchmarks across Cisco, Juniper, and Fortinet devices, achieving an 82.18% reduction in hardening time compared to prior automation tools and a 99.99% improvement over manual techniques. By leveraging Nornir’s multi-threading and vendor-agnostic inventory management, the framework ensures consistent security policies while eliminating configuration errors. Experimental results across 18 heterogeneous devices demonstrate its efficiency, with full hardening completed in 44 s (95% CI [43.8, 44.1]). This work provides enterprises with a scalable solution to rapidly secure complex networks against evolving threats, bridging the gap between compliance standards and real-world deployment.